2008
DOI: 10.3748/wjg.14.2977
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal papillary mucinous neoplasms and other pancreatic cystic lesions

Abstract: Pancreatic cystic neoplasms are being increasingly recognized, even in the absence of symptoms, in large part, due to markedly improved imaging modalities such as magnetic resonance imaging (MRI)/magnetic resonance cholangio pancreatography (MRCP) and computer tomography (CT) scanning. During the past 2 decades, better imaging of these cystic lesions has resulted in definition of different types, including pancreatic intraductal papillary mucinous neoplasms ( I P M N ) . W h i l e I P M N r e p r e s e n t o n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…International consensus guidelines 56 recommend resection in presence of high‐risk stigmata, while in presence of “worrisome features” the lesion should be evaluated by EUS to further risk‐stratify the lesion. Most IPMNs are asymptomatic and incidentally found during clinical evaluation for other conditions; when symptoms occur, they are generally related to intermittent obstruction of the pancreatic duct caused by thick mucin produced by the neoplasm 59 …”
Section: Intraductal Papillary Mucinous Neoplasms – Ipmnsmentioning
confidence: 99%
“…International consensus guidelines 56 recommend resection in presence of high‐risk stigmata, while in presence of “worrisome features” the lesion should be evaluated by EUS to further risk‐stratify the lesion. Most IPMNs are asymptomatic and incidentally found during clinical evaluation for other conditions; when symptoms occur, they are generally related to intermittent obstruction of the pancreatic duct caused by thick mucin produced by the neoplasm 59 …”
Section: Intraductal Papillary Mucinous Neoplasms – Ipmnsmentioning
confidence: 99%
“…The overall 5-year survival rate has been reported to exceed 80% for noninvasive IPMNs and 50% for the invasive malignant IPMNs [19] . Therefore, correct evaluation of IPMN is extremely important as a recent analysis has suggested that this entity is one of the few surgically curable pancreatic neoplasms [18] .…”
Section: Discussionmentioning
confidence: 99%
“…After the first report of IPMN in 1982, this tumor entity has been increasingly recognized over the past decades as a result of the markedly improved imaging modalities [18,19] . IPMNs mainly occur in the 6th to 7th decades of life, affecting males slightly more frequently than females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraductal papillary mucinous neoplasm (IPMN) is an increasingly reported entity, representing up to one third of all pancreatic cystic neoplasms [1] . IPMNs typically present with cystic dilatation of the pancreatic duct associated with mucin production and variable cellular atypia.…”
Section: To the Editormentioning
confidence: 99%